Translation of the literary work “Camino a Yangana” for the development of EFL reading comprehension skills of intermediate level baccalaureate students. - Garzón Bermeo, Marcela Eduarda (2023)
The following project consists of a translation of the Ecuadorian fantasy novel “Camino a Yangana”, along with follow-up activities and a glossary appendix, aiming at creating culture-bound, context-based materials to be used within the EFL classroom to help intermediate level students enhance their reading comprehension skills. This project emerged to supply EFL students with newer materials and resources for their learning process, as well as bringing a newer focus on Ecuadorian fantasy literature, which allows an exploration of different translation methods and techniques that fit the literary work chosen as the source of analysis. Said analysis was carried out to put forward a wider understanding of the translation field. The approaches taken into consideration were applied as a way to allow teenagers to boost learning of a language through content that feels fresher and more topical to them than outdated textbooks. The rendering of the literary work intends to make a Spanish language novel available for students, a literary work that, besides speaking of and exploring their experiences, could also allow recent Ecuadorian novels to find a spotlight in a newer, more global space; its English counterpart reframes cultural aspects in a manner that does not feel alien or too complex for EFL students to comprehend. The translation methods used for the selected literary work; communicative and faithful translation; in order reproduce a comprehensible message taken from the original source, constrained at times by the grammatical structures of the target language—following the literary genre but transferring the message accordingly.